Faktor-faktor yang Mempengaruhi Penguasaan Matematika Dasar pada Mahasiswa Baru Teknik Sipil dan Pertambangan: Peran Latar Belakang Pendidikan Menengah - Kamil, Firmanilah (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
In the context of this discussion, research was conducted to understand the challenges in understanding basic mathematics among students majoring in civil and mining engineering. Data were collected through questionnaires, interviews and tests to provide a comprehensive view. The questionnaire results revealed that most students felt confident in some aspects of basic mathematics, but some felt insecure with obstacles such as difficulty understanding concepts, difficulty remembering formulas, and lack of rigor. Interviews provided additional insights by revealing the reasons behind the level of confidence or lack of confidence. Test results showed that the majority of students still needed to improve their understanding of basic mathematics, and none were able to answer all questions correctly. In addition, there was a relationship between school of origin and test results, although most students came from senior high schools. Therefore, improvements in learning strategies and additional support are needed to help all students improve their understanding of basic mathematics, regardless of their school of origin, with the aim of improving their success in civil and mining engineering studies. As such, these results provide a foundation for improvements in the learning of basic mathematics, involving improvements in the way the material is taught, special attention to the most difficult-to-understand concepts, and support for students facing difficulties, to ensure better understanding of basic mathematics for all students.